Warming reduces the effects of enrichment on stability and functioning across levels of organisation in an aquatic microbial ecosystem. (15th April 2019) - Tabi, Andrea; Petchey, Owen L.; Pennekamp, Frank
Abstract: Warming and nutrient enrichment are major environmental factors shaping ecological dynamics. However, cross‐scale investigation of their combined effects by linking theory and experiments is lacking. We collected data from aquatic microbial ecosystems investigating the interactive effects of warming (constant and rising temperatures) and enrichment across levels of organisation and contrasted them with community models based on metabolic theory. We found high agreement between our observations and theoretical predictions: we observed in many cases the predicted antagonistic effects of high temperature and high enrichment across levels of organisation. Temporal stability of total biomass decreased with warming but did not differ across enrichment levels. Constant and rising temperature treatments with identical mean temperature did not show qualitative differences. Overall, we conclude that model and empirical results are in broad agreement due to robustness of the effects of temperature and enrichment, that the mitigating effects of temperature on effects of enrichment may be common, and that models based on metabolic theory provide qualitatively robust predictions of the combined ecological effects of enrichment and temperature.